2016
DOI: 10.1039/c6ob01803c
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of 6-DMATSMofrom Micromonospora olivasterospora leading to identification of the divergence in enantioselectivity, regioselectivity and multiple prenylation of tryptophan prenyltransferases

Abstract: Prenylated secondary metabolites including indole derivatives usually demonstrate improved biological and pharmacological activities, which make them promising candidates for drug discovery and development. The transfer reactions of a prenyl moiety from a prenyl donor, e.g. dimethylallyl diphosphate (DMAPP), to an acceptor is catalysed by prenyltransferases. One special group of such enzymes uses DMAPP and tryptophan as substrates with dimethylallyltryptophans as reaction products and functions therefore as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Since studies on other DMATS showed substrate promiscuity, the substrate scope of DMATS1 Ff was surveyed by testing different trypthophan derivatives and structurally related compounds (Figure S6). For substrates missing either the free amino group or the free carboxylic acid group no product formation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Since studies on other DMATS showed substrate promiscuity, the substrate scope of DMATS1 Ff was surveyed by testing different trypthophan derivatives and structurally related compounds (Figure S6). For substrates missing either the free amino group or the free carboxylic acid group no product formation was observed.…”
Section: Resultsmentioning
confidence: 99%
“…The engineering of an aminotransferase displaying near-native catalytic efficiency toward d -tryptophan (DAAT-V33G/T242G) was key to improve the performance of this procedure, which compensates for the unavailability of a d -selective TrpS. Many of the substituted d -tryptophans that we synthesized in preparative scale using our one-pot procedure are useful synthetic building blocks for a broad range of target molecules such as mitragynine and related 9-methoxy-substituted indole alkaloids (from d - 2d ), prenylated tryptophans (from d - 2f and d - 2i ), inhibitors of breast cancer resistance protein (from d - 2j ), and necrostatins (from d - 2k ). The biocatalytic approach developed here allows for the efficient synthesis of useful chiral synthons for the preparation of complex natural products and pharmaceutical ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…IptA, 5-DMATS Sc , and 6-DMATS Mo preferred DMAPP as a cosubstrate. 61,63,64,115,122 Of the three, only 6-DMATS Mo accepted GPP as a cosubstrate, but with a low turnover rate. 64 In contrast, PriB was reported to incorporate GPP with a turnover rate near 100%, demonstrating that the CPDR was not the only structural factor determining the cosubstrate scope, if at all.…”
Section: Structure Mechanism and Engineering Of Dmatssmentioning
confidence: 99%
“…Whereas DKP DMATSs can accommodate relatively large substrates (i.e., DKPs, naphthalenes, and aszonalenins), Trp DMATSs primarily prenylate simple indole derivatives, although FgaPT2 and PriB are notable exceptions (Table 1). 54,58,59,[61][62][63]65,[114][115][116][117][118][119] These two Trp DMATSs prenylated the indole moiety of the large antibiotic daptomycin, the structural basis of which has not yet been fully dened. 65 The ability of PriB, FgaPT2, and CdpNPT (the only three DMATSs shown to modify daptomycin) to generate prenylated daptomycin analogues provides a convenient starting point for the discussion of the steric constraints of the binding pockets of Trp DMATSs relative to those of DKP DMATSs.…”
Section: Reviewmentioning
confidence: 99%